2022
DOI: 10.3390/ani12030296
|View full text |Cite
|
Sign up to set email alerts
|

Social Stimulation by the Owner Increases Dogs’ (Canis familiaris) Social Susceptibility in a Food Choice Task—The Possible Effect of Endogenous Oxytocin Release

Abstract: Recent evidence suggests a human-like susceptibility to social influence in dogs. For example, dogs tend to ignore their ‘natural’ preference for the larger amount of food after having seen a human’s explicit preference for a smaller quantity. However, it is still unclear whether this tendency to conform to the partner’s behaviour can be influenced by social stimuli and/or the neurohormone oxytocin as primers to prosocial predispositions. In Experiment I, eighty two dogs were tested using Prato-Previde et al.’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…For visual comparison, the “change in bias” scores of dogs adopted from a shelter, therapy dogs and pet dogs from both the current and our previous study [ 10 ] are provided in Table 1 . for the available pre-treatment conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For visual comparison, the “change in bias” scores of dogs adopted from a shelter, therapy dogs and pet dogs from both the current and our previous study [ 10 ] are provided in Table 1 . for the available pre-treatment conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that social priming (i.e. social stimulation provided by the owner) has the potential to increase pet dogs’ social susceptibility in a similar way as would an intranasal oxytocin treatment [ 10 ]. It has been also shown that the oxytocin-increasing effect of social interactions depends on the relationship between the interacting partners [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations